PEMANFAATAN MEDIA (POWER POINT) UNTUK MENINGKATKAN AKTIVITAS DAN HASIL BELAJAR PESERTA DIDIK PADA MATA PELAJARAN IPS MATERI POKOK MANUSIA SEBAGAI MAHLUK SOSIAL DAN EKONOMI KELAS VII. A SEMESTER GANJIL DI SMP NEGERI 1 ARJASA SITUBONDO - Tri Astindari (STKIP PGRI SITUBONDO, 2016)
The teacher as a professional educator should be able to act as a communicator and facilitator for learners in the class. As a teacher communicators must be able to convey the message of learning to students. The purpose of this research is to improve the activity and student learning outcomes through the implementation of a powerpoint media in social studies / Economics Human Beings subject matter of social and economic class VII. A Semester At SMP Negeri 1 Arjasa, the object of research is VII.A graders 32 people. The design of this study is a model scheme mengguanakan Hopkins Tagart with 4 phases: planning, action / action, observation and reflection. To obtain the data in this study using the method of observation, interviews and tests. Data analysis in this study used a qualitative descriptive analysis. Based on the results obtained from observations of student activity, from the observation of student activity on the implementation of the second cycle is apparent there is an increase in the average scores compare that achieved in the implementation of the first cycle is 85.68% to 93.49%, the highest increase in activity occurred in student activity in attention to teachers' notes and worksheets memngerjakan given by the teacher. In the results of observations conducted by researchers and observers membukktikan 1 that there is an increase in the activity of student learning in social studies learning eye using powerpoint media. Based on the data obtained from the results of the daily tests students' mastery learning is known that the percentage of students in the classical style on the second cycle of 87.50%, and there are 4 students who still have not been thoroughly studied individually. For data on the percentage of students in the classical activity of 93.49% and an excellent activity criteria. From all the research that has been carried out then the researcher can take the conclusion that the eyes of Learning learning learning through the application of IPS with the use of powerpoint media can increase the activity of Class VII students. A Semester in SMP Negeri 1 Arjasa Situbondo the.